An efficient vector Preisach hysteresis model based on a novel rotational operator - Sutor, Alexander; Kallwies, Jan; Lerch, Reinhard (Journal of Applied Physics, 2012)
The vectorial modeling of hysteresis phenomena is an important task with respect to precise numerical simulation of ferromagnetic materials. Many vector models are based on extended Preisach models. Approaches are known where the scalar Preisach models are defined in different space directions and the results are calculated by summation or integration. Within this approach, we suggest a Preisach model that uses only one Preisach plane, but an additional rotational plane. This rotational plane practically defines a direction for each Preisach element. Therefore, this operator can be evaluated in a very efficient way. (C) 2012 American Institute of Physics. [doi: 10.1063/1.3672069]